1984
DOI: 10.3109/00365598409182179
|View full text |Cite
|
Sign up to set email alerts
|

Partial Cystectomy for Transitional Cell Carcinoma of the Bladder

Abstract: Partial cystectomy was performed for urothelium-derived bladder carcinoma in 55 patients in the period 1958-78. Ureteral re-implantation was done in 14 cases. The operative mortality was 7.3%. The five-year and ten-year survival rates were, respectively, 47.1 and 35.4%. The series was subdivided according to grade and T-stage of the tumours. The patients with a grade I or II tumour had significantly better survival rates than those with a grade III or IV tumour. T1 tumours had a more favourable outcome than T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…The 5-year survival rate in highly selected group of patients varies from 80 to 6% (table 3) [38,39], Local recurrence rate ranges from 30 to 78% [38][39][40][41], The recurrent tumors mainly occur during the first 2 post o p erativ e years [40], Radiotherapy is given pre-or postope rative to prevent tumor seeding within the incisional wound. Based on a literature review, Sweeney et al indicated that about 5-19% of patients undergoing cystectomy would be candidates for partial cystectomy [42], The actual place of partial cystectomy cannot be estimated by the current reports, because all of these publications deal with retrospective analy sis of highly selected patients treated with varying indications over a period of many years.…”
Section: Partial Cystectomymentioning
confidence: 99%
“…The 5-year survival rate in highly selected group of patients varies from 80 to 6% (table 3) [38,39], Local recurrence rate ranges from 30 to 78% [38][39][40][41], The recurrent tumors mainly occur during the first 2 post o p erativ e years [40], Radiotherapy is given pre-or postope rative to prevent tumor seeding within the incisional wound. Based on a literature review, Sweeney et al indicated that about 5-19% of patients undergoing cystectomy would be candidates for partial cystectomy [42], The actual place of partial cystectomy cannot be estimated by the current reports, because all of these publications deal with retrospective analy sis of highly selected patients treated with varying indications over a period of many years.…”
Section: Partial Cystectomymentioning
confidence: 99%
“…In the 1950s, partial cystectomy became widely used to treat muscle-invasive bladder cancer (MIBC); however, due to its high recurrence rate (40-78%), together with the development of controllable urinary diversion technology and the application of total cystectomy with preservation of nerves and prostate, radical cystectomy has become the 'gold standard' for the treatment of MIBC (1)(2)(3). However, study results from a 30-year period indicate that the postoperative 5-year survival rate of radical cystectomy is only 40-60% (4).…”
Section: Introductionmentioning
confidence: 99%
“…Partial cystectomy can be combined with radiotherapy and lymph node dissection if results are shown to be improved thereby [8], Over a 25-year period we have continued to use partial cystectomy in selected cases of bladder carcinoma where TUR was considered inade quate or inaccessible [11], The main contraindication for partial cystectomy has been encroachment of the tumor on the bladder neck, multiplicity or evidence of unstable bladder urothelium [4][5][6][9][10][11][12], Ureteric involvement is not a contraindication for this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Important criteria include accurate assessment of the tumor with regard to size, multiplicity, depth of penetration, grade of malig nancy and precise site as well as careful evaluation of the rest of the bladder urothelium to detect early cancerous changes [6,[10][11][12]. The evident advantages of reduced operative mortality and morbidity with preservation of bladder function, avoidance of a stoma and preservation of potency make the choice of partial cystectomy, as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation